Українсько-швейцарські відносини в 1918–1926 рр.: особливості дипломатичної присутності - Матяш, І. (Український історичний журнал, 2020)
Мета дослідження полягає у з’ясуванні процесу інституційного становлення українсько-швейцарських відносин у 1918–1921 рр. та особливостей дипломатичної присутності УНР у
Швейцарії в 1918–1926 рр. Методологія спирається на принципи науковості, історизму, системності. У межах міждисциплінарного підходу використано загальнонаукові та спеціальнонаукові
методи, зокрема архівної евристики, історіографічного аналізу, зовнішньої і внутрішньої критики
джерела. Наукова новизна результатів дослідження полягає в реконструкції на підставі архівної інформації, опублікованих і неопублікованих джерел діяльності українських дипломатичних
та консульських представництв у Берні, Цюріху, Женеві та з’ясуванні персоналій учасників процесу становлення українсько-швейцарських відносин у 1918–1926 рр., функцій і завдань дипломатичних, консульських представництв. Висновки. Розвиток українсько-швейцарських відносин у 1918–1921 рр. зумовлений геополітичною та економічною ситуацією в Європі під час та після
завершення Першої світової війни. Економічна криза, що істотно вплинула на соціально-економічне становище Швейцарії, викликала інтерес швейцарської сторони до встановлення торгівельних відносин з Україною. Натомість для України налагодження дипломатичних відносин зі
Швейцарією мало велике значення не лише у плані двосторонніх контактів, а і як можливість опосередкованої взаємодії з державами Антанти та участі в роботі міжнародних організацій. Українська дипломатична присутність у Швейцарії тривала до 1926 р. Її ключова особливість, попри «офіціозний» статус, полягала у відкритості влади до потреб українського представництва. The purpose of the research is to clarify the process of formation of Ukrainian-Swiss relations
in 1918–1921 and to establish the peculiarities of Ukraine’s diplomatic presence in Switzerland in
1918–1926.The research methodology is based on the principles of scientific, historicism, systemic.
In the framework of interdisciplinary approach, general scientific and special-scientific methods are
used. During the discovery and research of historiographical and historical sources, the methods
of archival heuristics, historiographical analysis, external and internal criticism of the source were
the key. The scientific novelty of the research results is the reconstruction of archival information
revealed by the author in published and unpublished sources, the activities of the Ukrainian diplomatic
and consular missions in Bern, Zürich, Genève and clarification personalities of participants in the
process of Ukrainian-Swiss relations in 1918–1926, establishing functions and tasks of diplomatic
and consular representatives. Conclusions. The development of Ukrainian-Swiss relations in
1918–1926 was due to the geopolitical and economic situation in Europe during and after the end
of the World War I. The economic crisis, which significantly influenced the socio-economic situation
in Switzerland, caused the Swiss party’s interest in establishing trade relations with Ukraine. For
Ukraine, the establishment of diplomatic relations with Switzerland was of great importance not only
as the establishment of bilateral contacts, but also as an opportunity for indirect interaction with the
Entente states and participation in the work of international organizations. The status of the embassy
provided to the Ukrainian office in Switzerland confirmed the importance for the Ukrainian State of
establishing relations with the Swiss Confederation. This confirmed Switzerland’s visit to Ukraine’s
trade mission, the creation of consular offices in Zürich and Genève, Ukrainian-Swiss Chamber of
Commerce, Ukrainian Information Bureau. The diplomatic representation of the UPR in Bern formally
existed until 1926. A key feature of Ukraine’s diplomatic presence in Switzerland in 1918–1926 is the
"official" status and openness of the Swiss authorities to the needs of the missions.